(untitled) (Latakia University Journal -Biological Sciences Series, 2025)
This research was carried out at Tishreen University, Faculty of Agricultural Engineering, Department of Plant Protection, and field experiments were conducted in an unheated greenhouse, and for the agricultural season 2022-2023 in the village of Harisoun, which is located in the far north of Tartous Governorate on the administrative border with Latakia Governorate, which is about 7 km from the city of Banias, and whose height above sea level does not exceed 7-10 m, to evaluate the effectiveness of Evernia prunastri extractsIn reducing the infection of Tomato brown rugose fruit virus on tomato by estimating the percentage and severity of infection with the virus, and estimating some growth parameters, by watering seedlings with lichen extract in different concentrations 100 - 75 - 50 - 25 mg / ml, the results showed After 30 and 60 days of causing infection with brown wrinkle virus on tomatoes, a decrease in the incidence and severity of infection in plants infected with the virus and plants treated with lichen extract concentration of 100% compared to control plants infected with the virus and not treated with lichen extract, where the rate of decrease in the incidence and severity of infection reached 24% and 34.67% respectively for the first appointment (30 days), and reached 34.67% and 73.33% respectively for the second appointment (60 days), with significant differences between the treatments. The biometric measurements of the vegetative total also showed significant differences between all the treatments and all the studied indicators (length, width and area of the paper, and the area of the paper surface and its index), the treatment of lichen exceeded the concentration of 75 and 100% on the control treatment and for all previous indicators, so that the highest average of the paper flat index was recorded in the healthy witness which is 6.45 and the lowest in the control infected with the virus which is 2.45 ,while the lichen coefficients at concentrations of 75% and 100% recorded the best paper flat evidence compared to other transactions without significant differences between them